EFFECT OF GRATED CASSAVA AS SUBSTITUTE FOR WHEAT FLOUR IN PROCESSING STEAMED CAKE - Budi Santoso; Susi Imelda Siagian; Agus Wijaya (BPFP Faperta UNIB, 2014)
The objective of research were to determine the physical and chemical characteristics, and organoleptic of steamed cake with grated cassava as an ingredient substitute for wheat flour. Research used a Non Factorial Complety Randomized Block Design (RALNF) with 5 level of treatments and 3 replication. Level of treatments research : A (wheat flour 0% and grated cassava 100%), B (wheat flour 20% and grated cassava 80%), C (wheat flour 40% and grated cassava 60%), D (wheat flour 60% and grated cassava 40%), E (wheat flour 80% and grated cassava 20%), and F (wheat flour 100% and grated cassava 0%). Results showed that steamed cakes with added grated cassava had significantly effect on the texture, moisture content, lightness, and hue but ash content and chroma not significant. The average value of texture, lightness, chroma, hue, moisture content and ash content of steamed cake is 618,33-1.273,47 gf; 65.30-75.20%; 32.33-38.03%; 83,27-86,87o; 29.84-40.41%; and 0.39-0.79%. Carbohydrate, protein, crude fiber, and HCN of steamed cake with grated cassava 80% and 40% were 44.88% and 49.9%; 3.37% and 2.90%; 3.94% and 2.91%, 1.72 and 1,14 mg /100 g respectively.